2007
DOI: 10.1161/strokeaha.106.479311
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Characteristics Associated With Perinatal Arterial Stroke in the Preterm Infant

Abstract: Background and Purpose-Most perinatal arterial stroke (PAS) studies that investigated infant characteristics have excluded preterm infants from the study population. We sought to analyze the imaging findings and antenatal and perinatal risk factors in preterm infants with PAS. Methods-This was a hospital-based, case-control study of preterm infants. Case infants were confirmed by reviewing brain imaging scans and medical records (nϭ31). Three controls per case were individually matched with case infants from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 33 publications
3
71
1
2
Order By: Relevance
“…3). Preterm infants are known to be at high risk of HI injury (20). Therefore, we investigated the efficacy of LPS protection in P3 and P5 rat pups.…”
Section: Resultsmentioning
confidence: 99%
“…3). Preterm infants are known to be at high risk of HI injury (20). Therefore, we investigated the efficacy of LPS protection in P3 and P5 rat pups.…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not have matched controls. Benders and colleagues [8] also found that fetal heart rate abnormality and hypoglycemia were risk factor for perinatal stroke in premature neonataes. We know that 6 children in our cohort had fetal distress, and 2 had hypoglycemia in the neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 95%
“…We did have 6 children with meningitis, which has been described as a risk factor for stroke in term neonates [13,14]. Although prothrombotic risk factors have been described as a risk factor for stroke in term neonates [15], few of the infants in Benders' cohort [8] or ours received full prothrombotic workups, probably because they were unstable in the neonatal intensive care unit for prolonged periods and often had anemia from multiple blood draws required for ongoing care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations